Determination of Factors Associated with Low Birth Weight among Babies Born in Sulaimania City, Kurdistan-Iraq - Weli, Sardar (Journal of the Faculty of Medicine Baghdad, 2020)
Background: Low birth weight (LBW) is the main leading cause of infant death. It is contributing to a variety of short and long term poor health outcomes. Determination of risk factors associated with LBW is important to select a suitable action to prevent or reduce this outcome. Studies on LBW and maternal risk factors in the Kurdistan region of Iraq are scarce.Objectives: This study aimed to determine risk factors associated with Low birth weight in Sulaimania city, Kurdistan region of Iraq.Cases and Methods: This study was carried out in the Maternity Hospital in Sulaimania from first of July, 2019 to first of February, 2020. Participants were 300 randomly selected mothers who gave a live birth. The questionnaire form, which contains information about factors associated with low birth weight (infant’s weight at birth lower than 2.5 kg) were filled by collectors. Infants were weighed immediately after delivery, and the weight was recorded in addition to sex of the infants, gestational age (weeks), age of the mother, job of the mothers, mother’s educational levels, antenatal care attendance, gravidity, residency, exercise and history of chronic diseases of mothers were recorded.Results: The results of the present study indicate that LBW was reported in 44.7% of the participants. For the LBW group, 48.5% were males and 51.5% were females. The highest percentage of LBW was among those born preterm 75.4% and the lowest was among full term 24.6%. Many factors such as an employed mother (85.8%), no exercise during pregnancy (88.1%), residency in urban (61.9%), mothers with chronic diseases (86.6%) and low level of education (illiterate and primary) (67.9%) were found as the significant risk factors of LBW. However, other factors such as prenatal care visits, age of mothers and gravidity were not found to be associated with LBW.Conclusion: The current study concludes that multiple risk factors may be associated with LBW in Sulaimania city, Kurdistan region of Iraq. Gestational age (preterm delivery), working mothers, no regular exercise, urban residence, low level of education and mother’s diseases such as hypertension, respiratory conditions, chronic infections and diabetes mellitus were considered as the risk factors associated with LBW.